2011
DOI: 10.1038/bjc.2011.290
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation by combination human lymphokine-activated killer and dendritic cell therapy

Abstract: Background:Optimal cellular immunotherapy for cancer should ideally harness both the innate and adaptive arms of the immune response. Lymphokine-activated killer cells (LAKs) can trigger early innate killing of tumour targets, whereas long-term adaptive-specific tumour control requires priming of CD8+ cytotoxic lymphocytes (CTLs) following acquisition of tumour-associated antigens (TAAs) by antigen-presenting cells such as dendritic cells (DCs). As DCs stimulate both innate and adaptive effectors, combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…We have not used murine models because there are significant differences between the effects of reovirus in mouse and human systems; for example, human DC protect reovirus from NAb by internalizing the virus without cell toxicity or viral replication, whilst murine DC support reovirus replication and die after infection . Moreover, human data are more directly relevant to clinical application, and we have previously shown LAKDC represent a practical immunogenic mixed cell population, which can readily be prepared to clinical grade from patient blood …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have not used murine models because there are significant differences between the effects of reovirus in mouse and human systems; for example, human DC protect reovirus from NAb by internalizing the virus without cell toxicity or viral replication, whilst murine DC support reovirus replication and die after infection . Moreover, human data are more directly relevant to clinical application, and we have previously shown LAKDC represent a practical immunogenic mixed cell population, which can readily be prepared to clinical grade from patient blood …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the ability of both LAK cells and reovirus to mature iDC, an essential step for generation of antigen-specific adaptive T cell antitumor immunity. 25,28 However, whether this applies in the context of malignant ascites, which may contain immunosuppressive factors that might impede DC maturation, has not been addressed. The ability of LAK cells and reovirus to phenotypically mature iDC in the presence of ascites was investigated by flow cytometry.…”
Section: Lak Cells and Reovirus Can Mature Idc In The Presence Of Ascmentioning
confidence: 99%
See 2 more Smart Citations
“…LAK cells demonstrated potent in vitro cytotoxicity against tumor cells and led to the regression of established tumors in animal models [3,4]. In clinical studies, LAK cells had demonstrated modest efficacy against metastatic cancer such as renal cell carcinoma and melanoma [5]. Many patients with cancer were ineligible for TIL-based therapy because their TILs did not expand sufficiently.…”
Section: Introductionmentioning
confidence: 99%